Eksistensi Kurikulum Kolaboratif di Sekolah Dasar Berbasis Islam dalam Upaya Mempersiapkan Mutu Lulusan Unggul - Lesmana, Indra; Burhanuddin, Burhanuddin; Sunandar, Asep (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
: The curriculum is said to be the main capital that determines the success of learning in each educational unit. Each educational unit has characteristics and characteristics in managing and developingits curriculum based on the vision, mission, and goals of the school. The purpose of this study is to describe (1) the implementation of a collaborative curriculum in Islamic-based elementary schools, (2) the impact of the application of a collaborative curriculum on the quality of graduates. The research was conducted qualitatively with a multi-site study approach. The research location is at Baitul Makmur Islamic Elementary School and Al-Rifa'ie Modern Elementary School Malang. Data collection was conducted by semi-structured interviews, observations, and documentation studies. Checking the credibility of data is carried out by means of diligence of observation, triangulation, checking members, and discussion of fellow researchers. The results of this study show that (1) the application of the collaborative curriculum basically refers to the vision, mission and goals of the school which focuses on preparing the quality of superior graduates in terms of academics, skills, and character. (2) The impact of implementing a collaborative curriculum is that students when graduating from school have advantages including good morals and religion. Students are more skilled in English and Irab and can read, write, and even memorize the Qur'an and hadith. Students are also able to make achievements from various competition events at the subdistrict, city, and provincial levels.